Identification and Analysis of Full Scale Ventilation Events - Luca Savio; Sverre Steen (International Journal of Rotating Machinery)
The present paper deals with propeller ventilation in full scale. The paper is based on full scale monitoring data from an offshore supply ship during normal operation. The data was collected by the on-line monitoring system HeMoS, developed by Rolls Royce Marine. The data covering one year and a half of ship operations were made available within the framework of the Era-Net Martec project PropSeas. The ventilation events are identified by means of an analysis procedure based on fuzzy logic. The paper contains both a basic introduction to fuzzy logic and a detailed description of the analysis procedure. The analysis procedure is then adopted to process the available data, find ventilation events, and form a set which is further analyzed including weather observations.